Experts in uncertainty : social work in child protection : a thesis presented in partial fulfillment of the requirements of the degree of Master of Social Work at Massey University - Pakura, Shannon (Massey University, 2008)
This research examines what motivates child protection social workers and the factors which support them to continue practicing in New Zealand's statutory agency, Child Youth and Family. Child welfare services are under stress with increasing workloads. The work is difficult and the hours are long. Workers manage ambiguity, uncertainty and they make judgments that no other agency or professional is called upon to make, within a system that requires them to constantly reassess priorities and Attracting and retaining workers in the child protection field of practice is a priority for Child Youth and Family. The thesis examines the motivating factors which encourage a social worker to remain practicing in the statutory child protection field. Understanding and strengthening these factors may assist New Zealand's statutory child protection agency; Child Youth and Family to increase the capability, capacity and experience of its professional workforce. Two methods were used to gather information for this study; in-depth individual interviews and a focus group. An inductive approach Was used to identify common themes and challenges. The key findings of the research showed that the quality of supervision and the relationships with one's supervisor and other professionals are critical. Self-care is a priority for the individual and operational policies must be clear, concise and accessible. Business and social work values guide the leadership of the statutory child welfare organisation. Workloads need to be manageable. Services to Maori require re-investment. A culture of acknowledging and celebrating the achievements of the agency and its staff should be infused through out the organisation and the general public made aware of the efforts and hard work of these professionals. The findings have identified that the needs of statutory child protection social workers are modest. Providing the systems that help sustain them in their role and ensuring the support mechanisms are operating will assist Child Youth and Family to recruit and retain a competent, experienced and resilient workforce to support and provide services to New Zealand children and their families.
Keywords: Social work with children; Child welfare workers; Child welfare services, New Zealand; Child protection